Vascular Cognitive Disorder: A Diagnostic and Pharmacological Treatment Updating - Julieta Russo, Maria; Francisco Allegri, Ricardo (Current Psychopharmacology, 2014)
Cognitive impairment underpins some of the clinical spectrum of the cerebrovascular disease (CVD), as well as contributes to the patient´s impaired social and behavioral functioning, and the higher mortality. When cognitive function is affected by CVD, we name it as vascular cognitive impairment (VCI). The cognitive impairment may be mild, or may be severe enough to warrant a diagnosis of dementia. Pure vascular dementia is not common. Because of that the concept of mixed dementia has been included in the clinical diagnosis of VCI. Despite a general emphasis in the international literature on the primary and secondary prevention of CVD to avoid vascular dementia or their combination with Alzheimer’s disease, the controversy concerning their diagnostic criteria and optimal treatment is still open. Given its growing burden, the prevention and treatment of CVD and the spectrum of VCI are critical priorities for clinical care and research. We performed a selective review about the current status of vascular dementia, mild cognitive impairment due to CVD, and mixed dementia, with special emphasis on available evidence of pharmacological strategies for treatment and prevention from controlled clinical trials.
Keywords: Alzheimer' s disease